A Case of Acute Cerebral Aspergillosis Complicating Influenza A/H1N1pdm 2009 - Kim, Min Jae; Kim, Min-Kyung; Kang, Chang Kyung; Jun, Kang Il; Bang, Ji-Hwan; Park, Sang-Won; Oh, Myoung-don (Infection & chemotherapy, 2013)
Invasive aspergillosis is a rare complication in patients with influenza infection. Several cases of invasive pulmonary aspergillosis accompanying influenza infections were reported during the influenza A/H1N1pdm 2009. We encountered a case of acute cerebral aspergillosis in a patient with influenza A/H1N1pdm 2009 infection. A 24-year-old man with uncontrolled diabetes was diagnosed with influenza A/H1N1pdm 2009 infection. Initial evaluation indicated methicillin-sensitive Staphylococcus aureus pneumonia and diabetic ketoacidosis along with influenza. During his hospital course, multiple new rim-enhancing mass lesions not evident in the initial evaluation developed in the fronto-parietal cortical and subcortical white matter and right cerebellum. Pathology and culture results confirmed the presence of Aspergillus fumigatus. Surgical drainage combined with a total of 18 weeks of antifungal therapy resulted in complete resolution of the infection. This case demonstrates that cerebral aspergillosis can present alongside influenza in patients with diabetes or those under intensive care. Clinical suspicion of invasive aspergillosis is required for a definite diagnosis and better prognosis in such cases.